2021
DOI: 10.1108/lht-01-2021-0034
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of teachers’ information literacy based on information of behavioral data in online learning and teaching platforms: an empirical study of China

Abstract: PurposeAdvances in information technology now permit the recording of massive and diverse process data, thereby making data-driven evaluations possible. This study discusses whether teachers’ information literacy can be evaluated based on their online information behaviors on online learning and teaching platforms (OLTPs).Design/methodology/approachFirst, to evaluate teachers’ information literacy, the process data were combined from teachers on OLTP to describe nine third-level indicators from the richness, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 47 publications
(64 reference statements)
0
9
0
1
Order By: Relevance
“…Information literacy of library and information science professionals Information literacy is an essential skill for modern life, and it is an essential professional skill for library and information systems science researchers and practitioners (Li et al, 2021;Tse et al, 2022). Ali and Ahmed (2022) investigated the information literacy skills of Pakistan's university library and information science professionals.…”
Section: Transformation Of Librariesmentioning
confidence: 99%
“…Information literacy of library and information science professionals Information literacy is an essential skill for modern life, and it is an essential professional skill for library and information systems science researchers and practitioners (Li et al, 2021;Tse et al, 2022). Ali and Ahmed (2022) investigated the information literacy skills of Pakistan's university library and information science professionals.…”
Section: Transformation Of Librariesmentioning
confidence: 99%
“…They suggested that higher education institutions maintain subscriptions to the most required e-books databases and that the LIS professionals conduct orientations and information literacy programs to help their users. Readers may be interested in recent articles on literacy issues, like teachers' information literacy (Li et al ., 2021b), parents' health literacy (Batool et al ., 2022) and information literacy self-efficacy (Soroya et al ., 2021).…”
Section: Bibliometric Analytics On Educationmentioning
confidence: 99%
“…They discovered 14 research topics in this area which can help specialists in health and medical areas to grasp the structured morphology of the current COVID-19 research. Readers may also notice our wealth of articles on bibliometrics related to COVID-19 (Li et al ., 2021a; Shueb et al ., 2022; Loan and Shah, 2022; Riahinia et al ., 2022; Zhu and Lei, 2022; Danesh et al ., 2021; Saab et al ., 2021; Allen, 2021; Yari Eili and Rezaeenour, 2023; Nadi-Ravandi and Batooli, 2023) and healthcare (Balaei-Kahnamoei et al ., 2022).…”
Section: Bibliometric Analytics For Research Topicsmentioning
confidence: 99%
“…Therefore, according to our question setting, they did not encounter any issues using Facebook as a learning aid. Also, Hong Kong students and teachers generally have a high level of information literacy and are thus ready to use SNSs (Wang et al, 2021;Chan et al, 2020;Li et al, 2021).…”
Section: Illiteracy Is Not a Major Concernmentioning
confidence: 99%